DEMOTIVATING FACTORS AND LANGUAGE LEARNING STRATEGIES IN ENGLISH AS A FOREIGN LANGUAGE WRITING CLASSES : A Mixed Method Study at Selected High Schools in Cimahi - Noviantoro, Nuriska (2014)
Demotivation is a detrimental situation where students' motivational action is diminished by specific external or internal forces. In the state of being demotivated, students may resort to ineffective activities in the classroom. However, some students may feel a need to remotivate their condition through several strategies, including through the use of in-class and out-of-class self-regulated language learning strategies. Thus, this study was conducted to examine what factors contributed to students' demotivation in Indonesian EFL context as well as to investigate what language learning strategies students employed in their learning of EFL writing. The participants involved in the study were 110 students from two public senior high schools in Cimahi. A mixed method study, employing modified battery and interview, was selected. The analysis involved the use of exploratory factor analysis and descriptive analysis. The result was that four demotivating factors were extracted, namely teacher-related factors, students' lack of confidence in self-regulating their study, inadequate learning facilities, and text-related problems. The major agreement in the study revealed that teacher-related factors were the most demotivating factor to the students. Meanwhile, the most employed language learning strategies were metacognitive strategies, with cognitive strategies as the least employed strategies. In line with the finding of demotivating factors, the tendency that the students encountered difficulties in employing cognitive strategies, excluding using resources for receiving and sending messages, may be due to their inability to self-regulate their own learning. Thus, this study recommends related parties to consider the detrimental effects of student demotivation in the teaching and learning process. Further studies are advised to examine other possible demotivating factors in the Indonesian EFL context and its remotivating strategies that the students use in coping with their demotivation. Demotivasi adalah sebuah situasi yang mengganggu dimana tindakan motivasi siswa dihalangi oleh gangguan-gangguan tertentu secara internal atau eksternal. Dalam keadaan terdemotivasi, siswa mungkin akan memilih pada kegiatan-kegiatan yang tidak efektif di kelas. Akan tetapi, beberapa siswa mungkin merasa sebuah kebutuhan untuk meremotivasi kondisi mereka, termasuk melalui penggunaan strategi belajar bahasa yang diatur sendiri di kelas dan di luar kelas. Oleh karena itu, penelitian ini dilakukan untuk mengetahui faktor-faktor yang berkontribusi pada demotivasi siswa serta menginvestigasi strategi belajar bahasa apa yang digunakan dalam pembelajaran bahasa Inggris mereka. Partisipan yang terlibat dalam penelitian adalah 110 siswa dari dua SMA negeri di Cimahi. Metode penelitian campuran, yang menggunakan sebuah kuesioner yang dimodifikasi dan wawancara, pun dipilih. Analisa menggunakan analisa faktor eksploratori dan analisa deskriptif. Hasil penelitian menunjukkan bahwa empat faktor demotivasi ditemukan, bernama faktor yang terkait dengan guru, kurang percaya dirinya siswa dalam mengatur belajar, kurangnya fasilitas belajar, dan masalah terkait teks. Sebagian besar partisipan setuju bahwa faktor yang terkait dengan guru adalah faktor yang paling mendemotivasi siswa. Sementara itu, strategi belajar bahasa yang paling sering digunakan adalah strategi metakognitif. Sesuai dengan temuan akan faktor yang mendemotivasi, kecenderungan siswa mengalami kesulitan dalam menggunakan strategi kognitif, dimana tidak termasuk menggunakan sumber-sumber untuk menerima dan mengirim pesan, mungkin dikarenakan ketidakmampuan mereka mengatur sendiri pembelajaran mereka. Oleh karena itu, penelitian ini merekomendasikan pihak-pihak yang terkait untuk mempertimbangkan efek yang kurang baik dari demotivasi siswa dalam proses belajar dan mengajar. Penelitian lebih lanjut disarankan untuk mengetahui faktor-faktor demotivasi lainnya dalam konteks pembelajaran bahasa Inggris di Indonesia dan usaha-usaha remotivasi yang siswa gunakan untuk mengatasi demotivasi mereka